Development and validation of contextual measures of sexual harassment perceptions, experiences, and coping for women employees in Ethiopian hospitality workplaces - Mulugeta Dile Worke; Zewdie Birhanu Koricha; Gurmesa Tura Debelew (BMC, 2022)
Abstract Background Sexual harassment among female employees in the hospitality industry is a complex phenomenon, and it has ramifications for employment, psychological, physical, and reproductive health. Nevertheless, our interpretation is constrained by a lack of agreement on its definition and measurement. As a result, hospitality workplaces require accurate tools that provide a detailed understanding of sexual harassment and inputs for action to limit adverse outcomes. Thus, this study aimed to develop a reliable and valid measure of female hospitality employees' perceptions, experiences, and coping features concerning sexual harassment. Methods Item development, scale development, and scale evaluation were all parts of the design process. Following a round of feedback from the expert group, qualitative results, and a comprehensive literature review on related themes, item pools were created for the first version of the questionnaire. Pre-testing, survey administration, item reduction, and transformation of extracted latent factors of individual items into a unified and measurable construct were also performed. Field testing included five cognitive interviews with women who had experienced sexual harassment, a pre-test study of 30 women, and a survey of 345 women who worked in hospitality workplaces. Finally, tests for dimensionality, reliability, and validity were conducted. Results In Bahir Dar, Ethiopia, 345 women working in the hospitality workplaces, with a mean age of 24.31 ± 4.30 years, took part in this study. The robust maximum likelihood estimation approach was used to do confirmatory factor analysis. The model's stability was determined by calculating the goodness of fit and the factorial invariance. Subsequently, the validity was confirmed. The findings supported the validity and reliability of the questionnaires designed for the target group. Therefore, the questionnaires can be used as research instruments. Conclusions The sexual harassment perceptions, experiences and coping scales provide a locally verified method for assessing sexual harassment in Ethiopia by government authorities and local and international non-governmental organisations, which aid in providing necessary services and the evaluation of efforts aimed at improving workplace safety, workplace health, and psychosocial well-being.